Exploring neolocalism among Finger Lakes breweries and local communities: Merits and cautions. Issue 2 (2nd July 2020) - Talmage, Craig A.; Denicourt, Julien C.; Delpha, Patrick J.; Goodwin, Gabriella B.; Snyder, Eleanor B.
ABSTRACT: Neolocalism has much to offer the local development literature. Highly discussed in the food and beverage tourism literature, neolocalism has shown merits for marketing place-based aspects of craft beverages to tourists and locals alike; however, few offer cautions against neolocalism, its limits, and its dark side. This article specifically examines how neolocalism is expressed among 41 breweries in the Finger Lakes region of New York. This article employs accessible research methods to identify expressions of neolocalism and to create a rubric to assess neolocalism, including location, naming, and storytelling. Using an online platform for consumer ratings, neolocalism correlated with brewery ratings in addition to other brewery attributes and beer ratings evaluated. Exemplars of neolocalism are featured, so others can see more in-depth examples of how it is expressed. Finally, implications for future research, policy, and practice are shared highlighting the merits and cautions regarding neolocalism.